Non-invasive mechanical ventilation in severe acute respiratory syndrome in patients hospitalized for COVID-19 - Sara Sabrina Vieira Cirilo; Raniel da Silva Machado; Alexandre da Conceição Santos; Karine Lima Rodrigues; Baldomero Antonio Kato da Silva (Instituto Politécnico de Viseu, 2022)
Introduction: Non-Invasive Ventilation is a form of ventilatory support that promotes improvement in several respiratory parameters such as peripheral oxygen saturation, decreased respiratory work, and a significant reduction in the need for intubation and mortality. It is a widely used therapy in the treatment of severe hypoxemia and refractory to oxygen therapy, a clinical condition observed in patients hospitalized for COVID-19. Objective: Investigate through the scientific literature the interference of Non-Invasive Ventilation in the hospital outcome of patients with severe acute respiratory syndrome triggered by COVID-19. Methods: The review will follow the guidelines established by the Joanna Briggs Institute methodology and Preferred Report Items for Systematic Reviews and Meta-Analyses. Two independent reviewers will perform the search, quality assessment, data extraction, and synthesis. The databases used will be PubMed, PEDro, Cochrane Central Register of Controlled Trials, Scielo, and Web of Science. Also, studies published in the grey literature in ProQuest Disserts and Theses Database Science and Google Scholar that meet established criteria will be included. Results: An initial survey showed that the proper use of Non-Invasive Ventilation administered with a helmet has significant outcomes on the rate of Orotracheal Intubation and Invasive Mechanical Ventilation. There were also studies with outcomes on morbidity and mortality and protocols for use and monitoring. Conclusion: The results will inform the use of this therapy and its outcomes to promote an effective intervention in hospitalized patients.